2008
DOI: 10.1016/j.colsurfa.2007.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic activity of silver-modified titanium dioxide at solid–liquid and solid–gas interfaces

Abstract: Silver-modified titania samples (Ag-TiO 2 ) with varying silver content (0.1-1.0 wt%) were prepared. Silver-modification of titanium dioxide was examined by TEM, XRD, XPS and DR-UV-vis spectroscopy. Ag or AgO x particles on TiO 2 surface could not be observed by XRD and TEM investigation, however the color of the Ag-TiO 2 samples varied between light rose and purple-brown. XPS measurements revealed that silver exists mainly in oxide form. The photocatalytic activity of pure and Ag-TiO 2 samples were compared b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 29 publications
3
17
0
Order By: Relevance
“…The use of chemical modifiers/dopants is one method of addressing the low transition temperature and issues regarding photocatalysis in TiO 2 . One type of doping involves the use of metal dopants such as iron [21][22][23][24], silver [15,25], chromium [26], copper [22,27,28], and manganese [29][30][31] or metal oxides such as Al 2 O 3 , SiO 2 and ZnO [11,14,[32][33][34]. However, as noted by Byrne et al the use of metal dopants can result in the formation of impurities at elevated temperatures which can have a negative impact on the transition temperature and photocatalytic activity [14,20,35].…”
Section: Introductionmentioning
confidence: 99%
“…The use of chemical modifiers/dopants is one method of addressing the low transition temperature and issues regarding photocatalysis in TiO 2 . One type of doping involves the use of metal dopants such as iron [21][22][23][24], silver [15,25], chromium [26], copper [22,27,28], and manganese [29][30][31] or metal oxides such as Al 2 O 3 , SiO 2 and ZnO [11,14,[32][33][34]. However, as noted by Byrne et al the use of metal dopants can result in the formation of impurities at elevated temperatures which can have a negative impact on the transition temperature and photocatalytic activity [14,20,35].…”
Section: Introductionmentioning
confidence: 99%
“…Since Fujishima's and Honda's pioneering work in 1972 [5], there has been a continuously growing interest in TiO 2 as a photocatalyst because of its efficiency, long term stability, cheapness and low toxicity [6][7][8][9]. Although TiO 2 is a good candidate for photocatalyst in general, especially in degradation of organic pollutants both in gas phase [7,10] and in liquid phase [7,[11][12][13] bare TiO 2 (in the absence of metal co-catalyst) results only in poor H 2 evolution in reaction (1) [14,15]. The activity of TiO 2 in the hydrogen producing reaction can be increased at least by an order of magnitude when a proper co-catalyst is involved [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Pure TiO 2 shows the smallest change, while COMP-Ag70 shows the largest change. Kőrösi et al showed that the rate of photooxidation of organic compounds was significantly enhanced by silver-modification of titania [39].…”
Section: Photo-responsive Activity Of Ag-np/tio 2 Composite Thin Filmsmentioning
confidence: 99%